Market share forecasting for banking offices - Lundsten, Lorman L. ([Ann Arbor, Mich.] : UMI Research Press, 1978)
This research seeks to develop and test a model of individual banking office choices.
Includes index.
Bibliography: p. [159]-163.
osc 09/05/2018
Loans
Keywords: Branch banks; Bank marketing; Banks and banking; Market share